2005
DOI: 10.1128/jb.187.4.1430-1440.2005
|View full text |Cite
|
Sign up to set email alerts
|

The Flag-2 Locus, an Ancestral Gene Cluster, Is Potentially Associated with a Novel Flagellar System from Escherichia coli

Abstract: Escherichia coli K-12 possesses two adjacent, divergent, promoterless flagellar genes, fhiA-mbhA, that are absent from Salmonella enterica. Through bioinformatics analysis, we found that these genes are remnants of an ancestral 44-gene cluster and are capable of encoding a novel flagellar system, Flag-2. In enteroaggregative E. coli strain 042, there is a frameshift in lfgC that is likely to have inactivated the system in this strain. Tiling path PCR studies showed that the Flag-2 cluster is present in 15 of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
121
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(127 citation statements)
references
References 54 publications
(64 reference statements)
6
121
0
Order By: Relevance
“…Y. pestis also possesses both dual-and single-domain FlgJ homologs, the latter of which is encoded by the flagellar gene cluster homologous to the lateral flagellar gene set of V. parahaemolyticus (Parkhill et al, 2003). After our database search presented here was finished, at least two additional bacterial strains, enteroaggregative E. coli strain 042 (Ren et al, 2005) and Aeromonas hydrophila strain AH-3 (Canals et al, 2006), have been reported to possess flagellar gene clusters homologous to the V. parahaemolyticus lateral flagellar gene set. These observations led to a hypothesis that the lateral flagellar gene set resides within a movable element and has been acquired by lateral gene transfer (Ren et al, 2005).…”
Section: Dual-domain Flgj In β-And γ-Proteobacteria and D Desulfuricmentioning
confidence: 99%
See 1 more Smart Citation
“…Y. pestis also possesses both dual-and single-domain FlgJ homologs, the latter of which is encoded by the flagellar gene cluster homologous to the lateral flagellar gene set of V. parahaemolyticus (Parkhill et al, 2003). After our database search presented here was finished, at least two additional bacterial strains, enteroaggregative E. coli strain 042 (Ren et al, 2005) and Aeromonas hydrophila strain AH-3 (Canals et al, 2006), have been reported to possess flagellar gene clusters homologous to the V. parahaemolyticus lateral flagellar gene set. These observations led to a hypothesis that the lateral flagellar gene set resides within a movable element and has been acquired by lateral gene transfer (Ren et al, 2005).…”
Section: Dual-domain Flgj In β-And γ-Proteobacteria and D Desulfuricmentioning
confidence: 99%
“…After our database search presented here was finished, at least two additional bacterial strains, enteroaggregative E. coli strain 042 (Ren et al, 2005) and Aeromonas hydrophila strain AH-3 (Canals et al, 2006), have been reported to possess flagellar gene clusters homologous to the V. parahaemolyticus lateral flagellar gene set. These observations led to a hypothesis that the lateral flagellar gene set resides within a movable element and has been acquired by lateral gene transfer (Ren et al, 2005). Our molecular data analyses on FlgJ described below support this hypothesis.…”
Section: Dual-domain Flgj In β-And γ-Proteobacteria and D Desulfuricmentioning
confidence: 99%
“…C. rodentium is a related A/E pathogen that infects mice, and it has recently provided a valuable animal model of human EHEC and EPEC infection and disease. While C. rodentium is described as nonmotile, its genome was recently released, and genes for two flagellins (FliC and Flag-2) were found within the C. rodentium genome (www .sanger.ac.uk/Projects/C_rodentium/) (33). To clarify whether C. rodentium is truly flagellin deficient, we assessed flagellin expression through immunoblotting using a mouse monoclonal antibody raised against pathogenic-E. coli flagella (and broadly cross-reactive against most flagellin types).…”
Section: Vol 76 2008 Epithelial Responses To Epec and C Rodentiummentioning
confidence: 99%
“…V. parahaemolyticus is the best-studied organism, and it has two distinct flagellar systems. Recently, an Escherichia coli O42 lateral flagellar gene cluster (Flag-2) has been described (33), and the presence of Flag-2-like gene clusters in Yersinia pestis, Yersinia pseudotuberculosis, and Chromobacterium violaceum suggests that the coexistence of two flagellar systems in the same species is more common than previously suspected (33). The polar flagellum (Fla) of V. parahaemolyticus requires around 60 genes distributed in five clusters on chromosome I for biogenesis and assembly (41), whereas lateral flagella (Laf) are coded for by 38 different genes distributed in two clusters on chromosome II (39).…”
mentioning
confidence: 99%